LITERARY IMAGE: NEED FOR A LEARNING QUALITY - Yuldosheva, Mamura (Журнал иностранных языков и лингвистики, 2023)
Descriptive writing is writing which utilizes imagery, or word pictures, to more fully engage the reader. While selected illustrations may work to an author’s advantage, they only do so much in terms of enhancing a written work. Through this article, it is going to discover literary image: need for a learning quality. Moreover, facts about the peculiarities of literary image were given.